Arabic-Islamic Views of the Latin West: Tracing the Emergence of Medieval Europe by Daniel G. König (Oxford: Oxford University Press, 2015. 464 pages.) (American Journal of Islam and Society, 2017)
Interactions between Latin Europeans and the Islamic world during the medievalperiod have received great attention in numerous scholarly studies. Thefocus of such works often consists of an attempt to delineate the constructionof identities and the extent to which they were utilized to mark out an “other.”By contrast, one of König’s most important conclusions demonstrates that formedieval Arab-Islamic scholars writing about the Latin West, these Latin Christiansocieties “were often simply regarded as alternative manifestations ofhuman life and its social and political organisation” (pp. 327-28).This is primarily a historiographical investigation with a macro-historicalapproach. König analyzes material spanning the early Islamic period (the seventhcentury) to the later medieval period (the fifteenth century) and covers arange of genres. It could be said that such an approach fails to critically analyzethe motivations of individual Muslim authors, something that the author doesacknowledge in his preface. However, such analyses lie beyond the scope ofthe project at hand. Furthermore, a macro-historical approach is necessary forchallenging previous scholarship on the subject. Bernard Lewis asserted thatthe Latin West was perceived as a united barbaric monolith, one viewed at bestwith disinterest in the minds of Muslim writers – a view that continues to influencescholarship to this day ...